MEDIA PENDIDIKAN PERSPEKTIF AL QURAN HADITS DAN PENGEMBANGANNYA - Mihmidaty Ya’cub (CENDEKIA: Jurnal Studi Keislaman, 2018)
Education is a basic need for the community to achieve progress. In the education process learning activities occur which in this case require media. Media education is a necessity to transfer information or knowledge to be more easily understood by students. In the early days of Islamic education, the Prophet has applied this educational media in conveying Islamic teachings to the Companions, using the Prophet's own behavior media, limbs, images, heaven and earth, sun and moon, silk and others. Along with the times, this educational media was later developed in the form of diagrams, graphics, globe, videos, tapes, power points and others.